Health in women on long-term sick leave because of pain or mental illness. Issue 1 (March 2015) - Lytsy, Per; Larsson, Kjerstin; Anderzén, Ingrid
Abstract : Mental illness and pain are common causes of long-term sick absence and major difficulties in vocational rehabilitation. The aim of this study was to investigate health in a group of women with pain or mental illness who had exhausted their days of sickness benefit. This cross-sectional study uses baseline data from 355 women on long-term sick leave participating in controlled intervention studies aiming at returning to work. The study population filled in a written questionnaire with questions of self-rated health and sleep quality and validated indexes of mental health, satisfaction with life and general self-efficacy. Clinical psychiatric screening was performed on 230 individuals. The study population had a mean age of 48.8 years (SD 8.4), with an average time on sick leave of 7.8 years (SD 3.2). Self-rated health and sleep quality was poor compared with other populations. In all, 80.1% had at least one psychiatric diagnosis according to the psychiatric screening, and the average numbers of psychiatric diagnoses were 2.2 (SD 1.9). Foreign-born women showed significantly higher levels of mental illness, poorer self-rated health and sleep quality and lower self-efficacy and life satisfaction than native Swedish women. Women with long sick leave because of mental illness and/or pain have poor self-rated health and sleep quality, high prevalence of mental illness and low self-efficacy and life satisfaction. Psychiatric screening suggests more extensive mental illness than what was stated on the sick leave certificates. The health of foreign-born women seems to be worse than that of native Swedish women.